Social and Institutional Barriers to Climate Change Mitigation in Agriculture - Dulal, Hari Bansha; Brodnig, Gernot (World Bank, Washington, DC, 2012)
Agriculture is one of the major sources of greenhouse gas (GHG) emissions accounting for approximately 14 percent of total GHG emissions. However, unlike other sectors such as transport or energy, agriculture is potentially a significant carbon 'sink'. Moreover, because the majority of GHG emissions from agriculture originate in developing countries, early intervention could be highly cost-effective. This note examines the potential role of agriculture in climate change mitigation. It discusses: 1) the sector's current GHG emissions, 2) its potential to serve as a sink, 3) best management practices that can be adopted to mitigate climate change, and 4) social and institutional barriers to adopting agricultural mitigation measures, and ways to overcome them.